THE INFLUENCE OF INTERNATIONALITY AND LOCATION ON DISCLOSURE OF INTELLECTUAL CAPITAL: A STUDIES IN HIGHER EDUCATION - Nika Esti Rahayu; Eko Arief Sudaryono (Universitas PGRI Madiun, 2023)
ABSTRACTThe research examines the effect of internationality and location on intellectual capital disclosure on the official website. The research method uses a quantitative approach with a total sample of 85 State Universities registered with UniRank 2021. Data analysis techniques use multiple linear regression analysis. The results showed that structural capital became the most dominant component of intellectual capital. The variables of internationality and location positively affect the disclosure of intellectual capital. The limitations of this study are that the samples and research variables still need to be improved. Despite the limitations, this study has practical implications as a reference for universities on the importance of internationality and location to the disclosure of intellectual capital.ABSTRAKPenelitan bertujuan menguji pengaruh internationality dan lokasi terhadap pengungkapan modal intelektual pada situs web resmi. Metode penelitian menggunakan pendekatan kuantitatif dengan jumlah sampel sebanyak 85 Perguruan Tinggi Negeri yang terdaftar UniRank 2021. Teknik analisis data menggunakan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa structural capital menjadi komponen modal intelektual yang paling dominan diungkapkan. Variabel internationality dan lokasi berpengaruh positif terhadap pengungkapan modal intelektual. Keterbatasan penelitian ini yaitu sampel dan variabel penelitian masih terbatas. Terlepas dari keterbatasan yang ada, penelitian ini berimplikasi praktis sebagai referensi untuk perguruan tinggi tentang pentingnya aspek internationality dan lokasi terhadap pengungkapan modal intelektual.